An analysis of students’ pronunciation errors of friction consonants in spoken production - Rella Islami; Gede Eka Putrawan; Fajar Riyantika (Lighthouse Publishing, 2021)
Pronunciation is an essential component of communicative competence, yet many EFL learners make pronunciation errors frequently. The English teacher in SMAS Global Madani Bandarlampung stated that students find it difficult to pronounce English words with certain consonants including friction consonants. The objectives of this research were to find out i) pronunciation errors of friction consonants that students made frequently and ii) the factors that influenced the errors. The approach of this research was qualitative. There were 20 students of the second grade chosen randomly. Performance assessment was used to collect the data. The data were analyzed by using the formula of Measures of Central Tendency. The data were also computed by using SPSS 26.0 for Windows. The result showed that the friction consonants that the students produced frequently were /v/ (31.5%) and /?/ (26%). In addition, the result of the students’ responses showed that the errors were caused by some factors. Those were exposure, first language (L1) background, lack of confidence, and attitude.